Evaluation of one-year mortality after geriatric ankle fractures in patients admitted to nursing homes. Issue 10 (October 2015) - Kadakia, Rishin J.; Hsu, Raymond Y.; Hayda, Roman; Lee, Yoojin; Bariteau, Jason T.
Abstract Introduction The incidence of geriatric ankle fractures will undoubtedly increase as the population continues to grow. Many geriatric patients struggle to function independently after such injury and often require placement into nursing homes. The morbidity and mortality associated with nursing homes is well documented within the field of orthopaedic surgery. However, there is currently no study examining the mortality associated with nursing home placement following hospitalization for an ankle fracture. Therefore, the purpose of this study was to determine if geriatric patients admitted to nursing homes following an ankle fracture experience elevated mortality rates. Methods Patients were identified using diagnosis codes for ankle fractures from all 2008 part A Medicare claims, and those admitted to nursing homes were identified using a Minimum Data Set (MDS). The Medicare database was also analyzed for specific variables including over-all one year mortality, length of stay, age distribution, certain demographical characteristics, incidence of medical and surgical complications within 90 days, and the presence of comorbidities. Multivariate logistic regression analysis was used to determine if patients admitted to nursing homes had elevated mortality rates. Results 19, 648 patients with ankle fractures were identified, and 11, 625 (59.0%) of these patients went to a nursing home after hospitalization. Patients who went to a nursing home had higher Elixhauser and Deyo–Charlson comorbidity scores (p < 0.0001). Nursing home patients also had significantly increased rates of postoperative medical and surgical complications. One year mortality was 6.9% for patients who did not go to a nursing home and 15.4% for patients who were admitted to a nursing home (p < 0.0001). However, multivariate logistic regression analysis demonstrated no significant difference in one year mortality between patients admitted to nursing homes and those who were not (OR = 1.1; 95% CI 0.99–1.24, p > 0.05). Discussion Although admission to nursing home was significantly associated with increased mortality in a bivariate statistical model, this significance was lost during multivariate analysis. This suggests that other patient characteristics may play a more prominent role in determining one year mortality following geriatric ankle fractures.